2017
DOI: 10.1128/mbio.01456-17
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Opal Stop Codon Attenuates Chikungunya Virus-Induced Arthritis and Pathology

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne alphavirus responsible for several significant outbreaks of debilitating acute and chronic arthritis and arthralgia over the past decade. These include a recent outbreak in the Caribbean islands and the Americas that caused more than 1 million cases of viral arthralgia. Despite the major impact of CHIKV on global health, viral determinants that promote CHIKV-induced disease are incompletely understood. Most CHIKV strains contain a conserved opal stop codon at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…Replacement of the opal stop codon by an arginine and cysteine residue, as was seen in isolates K3011 and P42214, respectively, has been described for other alphaviruses, including CHIKV and SINV (34,36), but this is the first time these mutations have been identified in the RRV genome. In addition, the loss of otherwise well-conserved proline-rich domains within the hypervariable domain (HVD) and the nucleotide deletions of various lengths that were observed in multiple isolates may have significant implications in terms of RRV replicative fitness, virulence, vector competence, and human pathogenesis that will need to be investigated.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Replacement of the opal stop codon by an arginine and cysteine residue, as was seen in isolates K3011 and P42214, respectively, has been described for other alphaviruses, including CHIKV and SINV (34,36), but this is the first time these mutations have been identified in the RRV genome. In addition, the loss of otherwise well-conserved proline-rich domains within the hypervariable domain (HVD) and the nucleotide deletions of various lengths that were observed in multiple isolates may have significant implications in terms of RRV replicative fitness, virulence, vector competence, and human pathogenesis that will need to be investigated.…”
Section: Discussionmentioning
confidence: 75%
“…Such opal stop codon-to-arginine transitions have been observed in several strains of other alphaviruses, including O'nyong-nyong virus (ONNV) (33) and CHIKV, and this is the first documented observation of such a transition in RRV. Introduction of an arginine codon into a CHIKV isolate significantly reduced joint morbidities in infected mice compared to that in mice infected with the wild type (34). Virus replication did not appear to be affected.…”
Section: Figmentioning
confidence: 90%
“…3A). Reports in the literature have also indicated that substitution of an arginine codon for the UGA codon of the CHIKIV TCR signals promoted reduced viral pathogenesis (13). When the TCR opal termination codon was mutated to an AGA arginine, 83.6 and 77.0% read-through efficiencies were observed for the Af/As and Carib consensus sequences, respectively (Fig.…”
Section: Targeted Mutations Alter Chikv Recoding Efficienciesmentioning
confidence: 81%
“…A closely associated downstream stimulatory element is thought to prevent efficient association of the eRF1-eRF3 complex with the ribosomes stalled at this codon, increasing the likelihood of a TCR event (12). The specific stop codon identity for this signal is critical for optimal alphavirus functionality as substitutions to amber or ochre stop codons or an arginine read-through have been associated with lowered transmission in mosquito vectors and significantly attenuated pathogenesis (13)(14)(15). The Ϫ1 PRF signal is located in the subgenomic RNA that encodes a polyprotein that is subsequently processed into structural proteins.…”
mentioning
confidence: 99%
“…The mutation opal524R in the nsP3-coding region was reported also by Mounce et al in the context of resistance selection against the compound DFMO [34], alongside with other nsP mutations. In the case of CHIKV and other alphaviruses (SFV, ONNV), evolutionary pressures have maintained both variants (stop and arginine codon) as it offers a fitness advantage when switching between vertebrate and invertebrate hosts [35][36][37]. The combination of the R171Q and opal524R mutations was also found independently during the selection of CHIKV variants that were resistant to an unrelated compound [38], and they merely appear to reflect adaptation to repeated passaging in mammalian cells (under stress).…”
Section: Suramin-resistant Chikv Variants Acquired Mutations In the Ementioning
confidence: 99%